The Relationship Between the Use of Injectable Contraceptives and Changes in Body Weight - Subiyatin, Aning; Zulfa, Susan; Hidayati, Elli; Jamil, , Siti (International Journal of Midwifery and Health Sciences, 2024)
Background: Injectable contraception is a contraceptive method made into a liquid and injected into the body. Some contain estrogen and progesterone once a month, but some only contain progesterone every three months. The most frequent side effect of contraception is weight gain. Depo Medroxy Progesterone Acetate (DMPA) stimulates the appetite control center in the hypothalamus, which causes acceptors to overeat. Excessive weight gain causes a number of diseases, such as obesity, hypertension, diabetes, and heart disease.Objective. Purpose : this study aims to analyze the relationship between the provision of injectable contraception and weight changes in PMB "X" Cilincing District, North Jakarta. Method : this type of research is quantitative with a cross-sectional design. The population is all KB acceptors at PMB NY "X" Cilincing District, North Jakarta, in 2022, totaling 110 respondents, and the sample is total sampling. Data processing with SPSS using the chi-square test. Results : The highest age is 20-35 years old, 78 (70.9%) people; most respondents have a college education, 49 (44.5%) people; more than half of respondents are homemakers, 61 (55.5%) people; the highest parity is one person, 63 (57.3%) people, and the longest time as a KB acceptor, the most respondents are more than one year, 65 (59.1%) people. In this study, it was also reported that respondents who experienced weight gain were 89 (90.9%) people, and 87 (79.1%) used a 3-month injection KB. The results of the statistical test obtained a value of p = 0.000 (p <0.05), which indicates a relationship between injection contraception and weight changes. Conclusion : There is a relationship between injection contraception and weight changes with a value of p = 0.000 (p <0.05).